Physical science - Tillery, Bill W. (McGraw-Hill, 2005)
Physical Science, Seventh Edition is a straightforward, easy-to-read, but substantial introduction to the fundamental behavior of matter and energy. It is intended to serve the needs of non-science majors who are required to complete one or more physical science courses. It offers exceptional, straight-forward writing, complimented with useful pedagogical tools. Tillery introduces basic concepts and key ideas while providing opportunities for students to learn reasoning skills and a new way of thinking about their environment. No prior work in science is assumed.